2007
DOI: 10.1002/ptr.2142
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of effectiveness of herbal antiinflammatory drugs in the treatment of painful osteoarthritis and chronic low back pain

Abstract: Treatment with herbal medicines is very popular in Europe. In order to get information on the evidence of effectiveness of oral herbal medicines in the treatment of pain in the joints or lower back, OVID(MEDLINE), PUBMED and COCHRANE COLLABORATION LIBRARY were searched back to 1985 for systematic reviews. The level of evidence of effectiveness was defined as strong - at least two confirmatory studies demonstrating a clinical relevant effect, moderate - one confirmatory study with a clinical relevant effect and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(65 citation statements)
references
References 83 publications
0
62
0
3
Order By: Relevance
“…Botanicals such as stinging nettle, 39 devil's claw, turmeric, and ginger 40 have yielded positive results, whereas avocado soybean fraction, rose hip, and seed powder showed moderate positive results and Boswellia serrata gum resin registered poor outcomes. 41 Previous studies using comfrey have all suggested that the herb is effective in treating edema 15,22 and pain associated with OA. Previous studies have found a 46% 42,43 and a 54.7% 24 reduction in OA knee pain following a regimen of comfrey cream use compared with a 10.7% improvement in a placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…Botanicals such as stinging nettle, 39 devil's claw, turmeric, and ginger 40 have yielded positive results, whereas avocado soybean fraction, rose hip, and seed powder showed moderate positive results and Boswellia serrata gum resin registered poor outcomes. 41 Previous studies using comfrey have all suggested that the herb is effective in treating edema 15,22 and pain associated with OA. Previous studies have found a 46% 42,43 and a 54.7% 24 reduction in OA knee pain following a regimen of comfrey cream use compared with a 10.7% improvement in a placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately most of the anti-inflammatory drugs, particularly steroids and cyclooxygenase inhibitors are often associated with adverse side effects including, GI irritation, ulcers, hypertension and cardiac abnormalities [5][6] . The use of herbal remedies for arthritis treatment has been gaining momentum in recent years [7] . There has been some concern over the use of COX-2 inhibitors for therapeutic intervention, especially since some of the products based on COX-2 were either withdrawn or made to carry warning by the US FDA [8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…The patients have been randomly assigned to receive an oral willow bark extract with either 120 mg (low dose) or 240 mg (high dose) of salicin, or placebo, with tramadol as the sole rescue medication, in a 4-week blinded trial. This research has indicated that Willow bark extract may be a useful and safe treatment for low back pain [39].…”
Section: White Willow Bark (Salix Alba)mentioning
confidence: 92%